The effects of drying process on bioactive compounds of fruits and vegetables - Yıldız, Gülçin; İzli, Gökçen (Nova Science Publishers, 2021)
Many bioactive compounds consist of antioxidants, vitamins, carotenoids, flavonoids, and other phenolics that exist in fruits and vegetables in appreciable amounts. Bioactive compounds have different biological activities such as scavenging reactive oxygen species (ROS), inhibiting oxidation and microbial growth, and reducing the risk of chronic diseases such as cancers and cardiovascular disorders. However, they have low stability against environmental conditions. Therefore, the drying process emerged to decrease their sensitivity and present a target delivery system. Dried fruits and vegetables can be easily stored and transported at a relatively low cost. They have reduced packing costs, and their low moisture content delays microbial spoilage. This review provides an overview of recent findings on the effects of different drying techniques on major bioactive compounds of fruits and vegetables. In particular, changes in ascorbic acids, carotenoids, flavonoids, phenolic acids, total phenolics, and antioxidant capacities are discussed in detail.